2021
DOI: 10.1002/ese3.869
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and damage of cement sheath in gas storage wells under cyclic loading

Abstract: The mechanical damage and failure of cement sheaths in gas storage wells under cyclic loading have been studied extensively. However, because the test device cannot restore the wellbore condition, most studies have been theoretical or regular experimental. If the load‐bearing mode and stress environment in a test device differ from those in a wellbore, then the damage and failure modes will deviate from what occurs in the actual wellbore. Therefore, it is necessary to explore a method that restores the wellbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Through previous research, a stress-equivalent method based on equalizing F I G U R E 2 Schematic of wellbore simulation test device the interface stresses of the first and second interfaces of the wellbore cement sheath and the cement sheath interface stress in the device was developed, as shown in Equation 1. 27 In particular, we ensured that the circumferential stress was equal on all sides by making the wellbore cement sheath proportional to the inner and outer diameters of the cement sheath in the device (1). Based on the equalization of the interface pressure (radial stress) between the wellbore cement sheath and the cement sheath in the device, the internal casing pressure and simulated formation confining pressure in the device were calculated (2).…”
Section: Equivalent Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Through previous research, a stress-equivalent method based on equalizing F I G U R E 2 Schematic of wellbore simulation test device the interface stresses of the first and second interfaces of the wellbore cement sheath and the cement sheath interface stress in the device was developed, as shown in Equation 1. 27 In particular, we ensured that the circumferential stress was equal on all sides by making the wellbore cement sheath proportional to the inner and outer diameters of the cement sheath in the device (1). Based on the equalization of the interface pressure (radial stress) between the wellbore cement sheath and the cement sheath in the device, the internal casing pressure and simulated formation confining pressure in the device were calculated (2).…”
Section: Equivalent Theorymentioning
confidence: 99%
“…25,26 Based on the principle that the first and second interface stresses of the cement sheath in the simulation device are equal to that of the wellbore cement sheath, Li et al tested the sealing ability of the cement sheath during the cyclic loading of gas storage wells and found that fatigue failure was the main cause of integrity failure. 27 Extensive research has been conducted to investigate the integrity of cement sheaths and their failure mechanisms; many shortcomings still exist. Prior simulations and tests focused mostly on the effect of high pressure or cyclic loading of the wellbore on the integrity of the cement sheath, ignoring the complex variants such as casing pressure test and the blow off that occur before acid fracturing and production.…”
Section: Introductionmentioning
confidence: 99%
“…However, cement is a heterogeneous material with numerous micropores, which can considerably influence the deformation and failure of cement sheaths under conditions of in situ stress and hydraulic fracturing [35][36][37] . At present, most researches on the deformation and failure of cement sheaths do not consider the effects of pore structure, and mainly focuses on the mechanical characteristics of cement sheaths, failure crack geometry, and damage laws [38][39][40][41][42][43] . Few studies have been conducted on the distribution characteristics of porous structures in cement sheaths and their influence on the stress distribution and deformation of cement sheaths, especially the effects on the failure mode and failure path of cement sheaths.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Mechanical failure and microannulus can significantly reduce the sealing ability of the cement sheath toward wellbore fluids, 10,12,13 resulting in failure of the hydraulic sealing. [14][15][16] In addition, a weak bonding strength at the interface and poor cementing quality can cause the cement sheath to lose its barrier function. 17,18 In recent years, some scholars further discovered that even if the cement sheath has good strength and deformation ability, the sealing failure of the cement sheath will also occur.…”
Section: Introductionmentioning
confidence: 99%
“…811 Mechanical failure and micro-annulus can significantly reduce the sealing ability of the cement sheath toward wellbore fluids, 10,12,13 resulting in failure of the hydraulic sealing. 1416 In addition, a weak bonding strength at the interface and poor cementing quality can cause the cement sheath to lose its barrier function. 17,18…”
Section: Introductionmentioning
confidence: 99%